Neurofibromatosis Type 1 Associated with Dysplastic Nevus Syndrome - Paštar, Zrinjka (Array, 2009)
Summary: Neurofibromatosis type 1 (NF-1) is an autosomal dominant disorder that primarily affects the development and growth of neural cell tissues. It causes tumors to grow on nerves and produces other abnormalities such as skin changes and bone deformities. Dysplastic nevus syndrome (DNS) represents multiple atypical nevi associated with polygenetic inheritance pattern and may rarely occur together with NF-1. DNS type A is a marker of increased melanoma risk, while melanoma has been rarely reported in patients with NF-1. We describe a case of NF-1 type A with DNS presenting with multiple neural tumors, cafe-au-lait spots, hamartomas in globus pallidus and pigmented melanocytic iris hamartomas (Lisch nodules). The importance of close follow up of nevi in such patients with NF-1 and DNS for the development of melanoma as well as other NF-1 associated skin disorders and with multidisciplinary approach to other associated diseases is highlighted